Citrus Land Values Decline as Other Land Values Increase: 2001 Survey Results: FE321/FE321, 10/2001 - Reynolds, John (EDIS, 2001)
This document is about the 2001 Florida Land Value Survey conducted by the University of Florida’s Food and Resource Economics Department. The survey reveals that agricultural land values increased across most types, except for citrus groves, which saw a decline. The document details the regional variations in land values, highlighting significant increases in cropland, pastureland, and farm woods. It also discusses the influence of nonagricultural factors on land values and provides insights into transition land values, which are significantly higher in urbanizing areas. The survey’s findings are based on the opinions of various professionals involved in the real estate market. Published first time Oct. 2001.